Reaction Kinetics Modeling of eHsp70 Induced by Norepinephrine in Response to Exercise Stress - Lovas, Attila; Szilágyi, Brigitta; Bosnyák, Edit; Ács, Pongrácz; Oláh, András; Komka, Zsolt; Tóth, Miklós; Merkely, Béla; Németh, Endre; Gilányi, Beatrix; Krepuska, Miklós; Sőti, Csaba; Sótonyi, Péter (International Journal of Sports Medicine, 2020)
Exercise elicits a systemic adaptation reaction, involving both neuroendocrine and cellular/paracrine stress responses, exemplified by the sympathoadrenergic activity and the release of cellular Hsp70 into the circulation. Regular sports training is known to result in increased fitness. In this study, we characterized the plasma norepinephrine and Hsp70 levels and modeled their relationship in response to exercise stress by bicycle ergometer in 12 trained judoka athletes and in 10 healthy controls. Resting norepinephrine was similar in both groups, whereas Hsp70 was significantly higher in controls compared to athletes. Intense exercise load induced both norepinephrine and Hsp70 elevation. However, both norepinephrine and Hsp70 were significantly lower in athletes compared to the control group. A reaction kinetic model was developed that provided a quantitative description of norepinephrine-facilitated extracellular Hsp70 release, congruent with the experimental data. Our study indicates that exercise-induced norepinephrine and extracellular Hsp70 may be coordinated responses to physiological stress, which are robustly affected by regular sports activity.
Keywords: reaction kinetics modeling; norepinephrine; Hsp70; exercise stress